Large Interruptions of GAA Repeat Expansion Mutations in Friedreich Ataxia Are Very Rare - Al-Mahdawi, Sahar; Ging, Heather; Bayot, Aurelien; Cavalcanti, Francesca; La Cognata, Valentina; Cavallaro, Sebastiano; Giunti, Paola; Pook, Mark A. (Frontiers in Cellular Neuroscience, 2018)
Friedreich ataxia is a multi-system autosomal recessive inherited disorder primarily caused by homozygous GAA repeat expansion mutations within intron 1 of the frataxin gene. The resulting deficiency of frataxin protein leads to progressive mitochondrial dysfunction, oxidative stress and cell death, with the main affected sites being the large sensory neurons of the dorsal root ganglia and the dentate nucleus of the cerebellum. The GAA repeat expansions may be pure (GAA)n in sequence or may be interrupted with regions of non-GAA sequence. To our knowledge there has been no large-scale study of FRDA patient DNA samples to determine the frequency of large interruptions in GAA repeat expansions. Therefore, we have investigated a panel of 245 Friedreich ataxia patient and carrier DNA samples using GAA repeat PCR amplification and MboII restriction enzyme digestion. We demonstrate that the vast majority (97.8%) of Friedreich ataxia GAA repeat expansion samples do not contain significant sequence changes that would result in abnormal MboII digestion profiles, indicating that they are primarily pure GAA repeats. These results show for the first time that large interruptions in the GAA repeats are very rare.